Tmem178 negatively regulates store-operated calcium entry in myeloid cells via association with STIM1. (July 2019) - Yang, Zhengfeng; Yan, Hui; Dai, Wentao; Jing, Ji; Yang, Yihu; Mahajan, Sahil; Zhou, Yubin; Li, Weikai; Macaubas, Claudia; Mellins, Elizabeth D.; Shih, Chien-Cheng; Fitzpatrick, James A.J.; et al.
Abstract: Store-operated calcium entry (SOCE) modulates cytosolic calcium in multiple cells. Endoplasmic reticulum (ER)-localized STIM1 and plasma membrane (PM)-localized ORAI1 are two main components of SOCE. STIM1:ORAI1 association requires STIM1 oligomerization, its re-distribution to ER-PM junctions, and puncta formation. However, little is known about the negative regulation of these steps to prevent calcium overload. Here, we identified Tmem178 as a negative modulator of STIM1 puncta formation in myeloid cells. Using site-directed mutagenesis, co-immunoprecipitation assays and FRET imaging, we determined that Tmem178:STIM1 association occurs via their transmembrane motifs. Mutants that increase Tmem178:STIM1 association reduce STIM1 puncta formation, SOCE activation, impair inflammatory cytokine production in macrophages and osteoclastogenesis. Mutants that reduce Tmem178:STIM1 association reverse these effects. Furthermore, exposure to plasma from arthritic patients decreases Tmem178 expression, enhances SOCE activation and cytoplasmic calcium. In conclusion, Tmem178 modulates the rate-limiting step of STIM1 puncta formation and therefore controls SOCE in inflammatory conditions. Graphical abstract: Image 1 Highlights: Tmem178 negatively regulates calcium fluxes in myeloid cells by modulating SOCE. Tmem178 binds to STIM1 and limits STIM1 puncta formation and association with Orai1. Tmem178 and STIM1 associate via their transmembrane domains. Tmem178: STIM1 association reduces macrophage responses and osteoclastogenesis.